Histopathological and Biochemical Comparative Study of Copper Oxide Nanoparticles and Copper Sulphate Toxicity in Male Albino Mice Reproductive System - Manal M. S. AL-Musawi; Hanady Al-Shmgani; Genan A. Al-Bairuty (International Journal of Biomaterials)
Copper (Cu) is an essential trace element for the efficient functioning of living organisms. Cu can enter the body in different ways, and when it surpasses the range of biological tolerance, it can have negative consequences. The use of different nanoparticles, especially metal oxide nanoparticles, is increasingly being expanded in the fields of industry and biomedical materials. However, the impact of these nanoparticles on human health is still not completely elucidated. This comparative study was conducted to evaluate the impacts of copper oxide nanoparticles (CuO NPs) and copper sulphate (CuSO4 0.5 (H2O)) on infertility and reproductive function in male albino mice BALB/c. Body weight, the weight of male reproductive organs, malondialdehyde (MDA) level, caspase-3 level, and the presence of Ki67 and CD68, as detected using the amino-histochemistry technique, were investigated. Animals were treated with 25 and 35 mg/kg of CuO NPs and CuSO4 0.5 (H2O) by oral gavage for 14 days. The control group was given distilled water by oral gavage. Body weight significantly decreased at the end of experiments in both treated groups in a concentration- and time-dependent manner compared with the control group. Weights of testes and epididymis (head and tail), as well as the weight of the seminal vesicle, showed a significant decrease compared with the control. However, the average weights of the seminal vesicle and prostate significantly increased. Caspase-3 and MDA levels increased in the CuO NP and CuSO4 0.5 (H2O) groups compared with the control group, and there was a significant difference between the two concentrations used. Immunohistochemical results detected a significant decrease in Ki67 protein in the treatment groups compared with the control. However, increase in CD68 protein was found in groups treated with CuO NPs and CuSO4 0.5 (H2O) compared with the control group. Overall, this in vivo comparative study of CuO NPs and CuSO4 0.5 (H2O) showed that oral intake of copper NPs at 25 and 23 mg/kg was safer to the mice reproductive system than CuSO4 0.5 (H2O) at the same dose. CuSO4 0.5 (H2O) significantly influenced the histopathological and toxicological alteration responses.